دور إدارة الجمارك في حماية المستهلك - الحرفي، سكينة (هشام الاعرج, 2022)
تلعب إدارة الجمارك دورا فعالا من خلال مراقبة المواد المستوردة والتدقيق في مدى خضوعها للمواصفات الإلزامية على المستوى الصحي وتوفير حماية الإنتاج الوطني وتحقيق العدالة الضريبية عن طريق محاربة انحراف الأسواق الوطنية بالسلع والبضائع الواصفة إليها ومحاربة الغش والتهريب. The Customs Administration plays an active role by monitoring imported materials, checking their compliance with mandatory health standards, providing protection for national production, and achieving tax justice by combating the deviation of national markets with goods and merchandise described to them, and combating fraud and smuggling.
Keywords: الجمارك -- الإدارة الجمركية -- الرقابة الجمركية -- حماية المستهلكين -- المغرب